Reliability of a novel serious game using dual-task gait profiles to early characterize aMCI - Tarnanas, Ioannis; Papagiannopoulos, Sotirios; Kazis, Dimitris; Wiederhold, Mark; Widerhold, Brenda; Tsolaki, Magda (Frontiers in Aging Neuroscience, 2015)
Background: As the population of older adults is growing, the interest in a simple way to detect characterize amnestic mild cognitive impairment (aMCI), a prodromal stage of Alzheimer’s disease (AD), is becoming increasingly important. Serious game (SG) -based cognitive and motor performance profiles while performing everyday activities and dual-task walking (DTW) “motor signatures” are two very promising markers that can be detected in predementia states. We aim to compare the consistency, or conformity, of measurements made by a custom SG with DTW (NAV), a SG without DTW (DOT), neuropsychological measures and genotyping as markers for early detection of aMCI. Methods: The study population included three groups: early AD (n = 86), aMCI (n = 65), and healthy control subjects (n = 76), who completed the custom SG tasks in three separate sessions over a 3-month period. Outcome measures were neuropsychological data across-domain and within-domain intra-individual variability (IIV) and DOT and NAV latency-based and accuracy-based IIV. IIV reflects a transient, within-person change in behavioral performance, either during different cognitive domains (across-domain) or within the same domain (within-domain). Test–retest reliability of the DOT and NAV markers were assessed using an intraclass correlation (ICC) analysis. Results: Results indicated that performance data, such as the NAV latency-based and accuracy-based IIV, during the task displayed greater reliability across sessions compared to DOT. During the NAV task-engagement, the executive function, planning, and motor performance profiles exhibited moderate to good reliability (ICC = 0.6–0.8), while during DOT, executive function and spatial memory accuracy profiles exhibited fair to moderate reliability (ICC = 0.3–0.6). Additionally, reliability across tasks was more stable when three sessions were used in the ICC calculation relative to two sessions. Discussion: Our findings suggest that “motor signature” data during the NAV tasks were a more reliable marker for early diagnosis of aMCI than DOT. This result accentuates the importance of utilizing motor performance data as a metric for aMCI populations where memory decline is often the behavioral outcome of interest. In conclusion, custom SG with DTW performance data provide an ecological and reliable approach for cognitive assessment across multiple sessions and thus can be used as a useful tool for tracking longitudinal change in observational and interventional studies on aMCI.